The Problems Encountered by Non-English Department Students in Speaking English - Yulia Galuh Tantri; Farid Noor Romadlon; Agung Dwi Nurcahyo (International Journal of Research in Education, 2023)
Speaking is one of the difficult English skills for non-English department students. This is because students must understand how to produce good and correct sentences to pronounce. To produce a sentence, they must master a lot of vocabulary and master how to pronounce it. In addition, to be able to master speaking skills, students must also have self-confidence. This research aimed to know the problems encountered by Non-English Department students in speaking English and their causes and to find out the problem-solving encountered by non-English majoring students in speaking English. The researcher used descriptive qualitative research with a questionnaire and an interview to collect the data. The results of this study indicate that almost all students find problems (linguistic and nonlinguistic) in speaking English. Linguistic problems that are often found are a lack of grammar, poor pronunciation, and the last is lack of vocabulary. The non-linguistics are anxiety, shyness & lack of confidence. The factors causing the problem of speaking English in this study were low motivation, habits & mother tongue, lack of practice & opportunity, and fear of making mistakes. To solve the problem of speaking English is to improve vocabulary and pronunciation skills. Some ways to improve it are by listening and singing English songs, watching English movies to understand English sentences, and using Google Translate to look up the meaning of difficult words and how to pronounce them. In addition, to improve their speaking skills, sometimes students also practice speaking in English with their friends or independently.